Antibacterial and antiparasitic effects of Bothrops marajoensis venom and its fractions: Phospholipase A(2) and L-amino acid oxidase - Costa Torres, Alba Fabiola; Dantas, Rodrigo Tavares; Toyama, Marcos H. [UNESP]; Diz Filho, Eduardo [UNESP]; Zara, Fernando Jose [UNESP]; Rodrigues de Queiroz, Maria Goretti; Pinto Nogueira, Nadia Accioly; de Oliveira, Marcia Rosa; Toyama, Daniela de Oliveira; Monteiro, Helena S. A.; Martins, Alice M. C. (Pergamon-Elsevier B.V. Ltd, 2010)
Some proteins present in snake venom possess enzymatic activities, such as phospholipase A(2) and L-amino acid oxidase. In this study, we verify the action of the Bothrops marajoensis venom (BmarTV), PLA(2) (BmarPLA(2)) and LAAO (BmarLAAO) on strains of bacteria, yeast, and Leishmania sp. The BmarTV was isolated by Protein Pack 5PW, and several fractions were obtained. Reverse phase HPLC showed that BmarPLA(2) was isolated from the venom, and N-terminal amino acid sequencing of sPLA(2) showed high amino acid identity with other lysine K49 sPLA(2)s isolated from Bothrops snakes. The BmarLAAO was purified to high molecular homogeneity and its N-terminal amino acid sequence demonstrated a high degree of amino acid conservation with others LAAOs. BmarLAAO was able to inhibit the growth of P. aeruginosa, C. albicans and S. aureus in a dose-dependent manner. The inhibitory effect was more significant on S. aureus, with a MIC = 50 mu g/mL and MLC = 200 mu g/mL However, the BmarTV and BmarPLA(2) did not demonstrate inhibitory capacity. BmarLAAO was able to inhibit the growth of promastigote forms of L chagasi and L amazonensis, with an IC50 = 2.55 mu g/mL and 2.86 mu g/mL for L. amazonensis and L. chagasi, respectively. BmarTV also provided significant inhibition of parasitic growth, with an IC50 of 86.56 mu g/mL for L. amazonensis and 79.02 mu g/mL for L chagasi. BmarPLA(2) did not promote any inhibition of the growth of these parasites. The BmarLAAO and BmarTV presented low toxicity at the concentrations studied. In conclusion, whole venom as well as the L-amino acid oxidase from Bothrops marajoensis was able to inhibit the growth of several microorganisms, including S. aureus, Candida albicans, Pseudomonas aeruginosa, and Leishmania sp. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: L-amino acid oxidase; Phospholipases A(2); Bothrops marajoensis